forked from cs3110/textbook-solutions
-
Notifications
You must be signed in to change notification settings - Fork 0
/
Copy pathchapter6b.txt
407 lines (305 loc) · 8.16 KB
/
chapter6b.txt
1
2
3
4
5
6
7
8
9
10
11
12
13
14
15
16
17
18
19
20
21
22
23
24
25
26
27
28
29
30
31
32
33
34
35
36
37
38
39
40
41
42
43
44
45
46
47
48
49
50
51
52
53
54
55
56
57
58
59
60
61
62
63
64
65
66
67
68
69
70
71
72
73
74
75
76
77
78
79
80
81
82
83
84
85
86
87
88
89
90
91
92
93
94
95
96
97
98
99
100
101
102
103
104
105
106
107
108
109
110
111
112
113
114
115
116
117
118
119
120
121
122
123
124
125
126
127
128
129
130
131
132
133
134
135
136
137
138
139
140
141
142
143
144
145
146
147
148
149
150
151
152
153
154
155
156
157
158
159
160
161
162
163
164
165
166
167
168
169
170
171
172
173
174
175
176
177
178
179
180
181
182
183
184
185
186
187
188
189
190
191
192
193
194
195
196
197
198
199
200
201
202
203
204
205
206
207
208
209
210
211
212
213
214
215
216
217
218
219
220
221
222
223
224
225
226
227
228
229
230
231
232
233
234
235
236
237
238
239
240
241
242
243
244
245
246
247
248
249
250
251
252
253
254
255
256
257
258
259
260
261
262
263
264
265
266
267
268
269
270
271
272
273
274
275
276
277
278
279
280
281
282
283
284
285
286
287
288
289
290
291
292
293
294
295
296
297
298
299
300
301
302
303
304
305
306
307
308
309
310
311
312
313
314
315
316
317
318
319
320
321
322
323
324
325
326
327
328
329
330
331
332
333
334
335
336
337
338
339
340
341
342
343
344
345
346
347
348
349
350
351
352
353
354
355
356
357
358
359
360
361
362
363
364
365
366
367
368
369
370
371
372
373
374
375
376
377
378
379
380
381
382
383
384
385
386
387
388
389
390
391
392
393
394
395
396
397
398
399
400
401
402
403
404
405
406
407
==========================================================
Exercise: exp
Claim: exp x (m + n) = exp x m * exp x n
Proof: by induction on m.
P(m) = exp x (m + n) = exp x m * exp x n
Base case: m = 0
Show: exp x (0 + n) = exp x 0 * exp x n
exp x (0 + n)
= { evaluation }
exp x n
exp x 0 * exp x n
= { evaluation }
1 * exp x n
= { evaluation }
exp x n
Inductive case: m = k + 1
Show: exp x ((k + 1) + n) = exp x (k + 1) * exp x n
IH: exp x (k + n) = exp x k * exp x n
exp x ((k + 1) + n)
= { evaluation }
x * exp x (k + n)
= { IH }
x * exp x k * exp x n
exp x (k + 1) * exp x n
= { evaluation }
x * exp x k * exp x n
QED
==========================================================
Exercise: fibi
Claim: forall n >= 1, fib n = fibi n (0, 1)
We need to strengthen the hypothesis for the induction to go through.
Lemma: forall n >= 1, forall m >= 1, fib (n + m) = fibi n (fib m, fib (m + 1))
Proof: by induction on n.
Base case: n = 1
Show: forall m >= 1, fib (1 + m) = fibi 1 (fib m, fib (m + 1))
fibi 1 (fib m, fib (m + 1))
= { evaluation }
fib (m + 1)
= { algebra }
fib (1 + m)
Inductive case: n = k + 1
Show: forall m >= 1, fib ((k + 1) + m) = fibi (k + 1) (fib m, fib (m + 1))
IH: forall m >= 1, fib (k + m) = fibi k (fib m, fib (m + 1))
fib ((k + 1) + m)
= { algebra }
fib (k + (m + 1))
= { IH with m := m + 1 }
fibi k (fib (m + 1), fib (m + 2))
= { evaluation }
fibi k (fib (m + 1), fib m + fib (m + 1))
fibi (k + 1) (fib m, fib (m + 1))
= { evaluation }
fibi k (fib (m + 1), fib m + fib (m + 1))
QED
We cannot apply the lemma directly because (fib m) is not equal
to 0 for any m. We proceed by breaking `n` into two cases.
Case 1: n = 1.
Show: fib 1 = fibi 1 (0, 1)
fib 1
= { evaluation }
1
fibi 1 (0, 1)
= { evaluation }
1
Case 2: n = k + 1, k >= 1.
Show: fib (k + 1) = fibi (k + 1) (0, 1)
fib (k + 1)
= { Lemma with n := k, m := 1 }
fibi k (fib 1, fib 2)
= { evaluation }
fibi k (1, 1)
fibi (k + 1) (0, 1)
= { evaluation }
fibi k (1, 1)
QED
==========================================================
Exercise: expsq
Claim: forall n x, expsq x n = exp x n
Proof: by induction on n.
P(n) = forall x, expsq x n = exp x n
Base case 0: n = 0
Show: forall x, expsq x 0 = exp x 0
expsq x 0
= { evaluation }
1
exp x 0
= { evaluation }
1
Base case 1: n = 1
Show: forall x, expsq x 1 = exp x 1
expsq x 1
= { evaluation }
x
exp x 1
= { evaluation }
x * exp x 0
= { evaluation and algebra }
x
Inductive case for even n: n = 2k
Show: forall x, expsq x 2k = exp x 2k
IH: forall x, forall j < 2k, expsq x j = exp x j
expsq x 2k
= { evaluation }
1 * expsq (x * x) (2k / 2)
= { IH, instantiating its x as (x * x)
and j as (2k / 2) }
exp (x * x) k
= { evaluation }
(x * x) * exp (x * x) (k - 1)
exp x 2k
= { evaluation }
x * exp x (2k - 1)
= { evaluation }
(x * x) exp x (2k - 2)
= { IH, instantiating its x as x and j as (2k - 2) }
(x * x) * expsq x (2k - 2)
= { evaluation and algebra }
(x * x) * expsq (x * x) (k - 1)
= { IH, instantiating its x as (x * x) and j as (k - 1) }
(x * x) * exp (x * x) (k - 1)
Inductive case for odd n: n = 2k + 1
Show: forall x, expsq x (2k + 1) = exp x (2k + 1)
IH: forall x, forall j < 2k, expsq x j = exp x j
expsq x (2k + 1)
= { evaluation }
x * expsq (x * x) ((2k + 1) / 2)
= { by the properties of integer division }
x * expsq (x * x) k
exp x (2k + 1)
= { evaluation }
x * exp x 2k
= { IH, instantiating its x as x, and j as 2k) }
x * expsq x 2k
= { evaluation and algebra }
x * expsq (x * x) k
QED
==========================================================
Exercise: mult
Claim: forall n, mult n Z = Z
Proof: by induction on n
P(n) = mult n Z = Z
Base case: n = Z
Show: mult Z Z = Z
mult Z Z
= { eval mult }
Z
Inductive case: n = S k
Show: mult (S k) Z = Z
IH: mult k Z = Z
mult (S k) Z
= { eval mult }
plus Z (mult k Z)
= { IH }
plus Z Z
= { eval plus }
Z
QED
==========================================================
Exercise: append nil
Claim: forall lst, lst @ [] = lst
Proof: by induction on lst
P(lst) = lst @ [] = lst
Base case: lst = []
Show: [] @ [] = []
[] @ []
= { eval @ }
[]
Inductive case: lst = h :: t
Show: (h :: t) @ [] = h :: t
IH: t @ [] = t
(h :: t) @ []
= { eval @ }
h :: (t @ [])
= { IH }
h :: t
QED
==========================================================
Exercise: rev dist append
Claim: forall lst1 lst2, rev (lst1 @ lst2) = rev lst2 @ rev lst1
Proof: by induction on lst1
P(lst1) = forall lst2, rev (lst1 @ lst2) = rev lst2 @ rev lst1
Base case: lst1 = []
Show: forall lst2, rev ([] @ lst2) = rev lst2 @ rev []
rev ([] @ lst2)
= { eval @ }
rev lst2
rev lst2 @ rev []
= { eval rev }
rev lst2 @ []
= { exercise 2 }
rev lst2
Inductive case: lst1 = h :: t
Show: forall lst2, rev ((h :: t) @ lst2) = rev lst2 @ rev (h :: t)
IH: forall lst2, rev (t @ lst2) = rev lst2 @ rev t
rev ((h :: t) @ lst2)
= { eval @ }
rev (h :: (t @ lst2))
= { eval rev }
rev (t @ lst2) @ [h]
= { IH }
(rev lst2 @ rev t) @ [h]
rev lst2 @ rev (h :: t)
= { eval rev }
rev lst2 @ (rev t @ [h])
= { associativity of @, proved in textbook }
(rev lst2 @ rev t) @ [h]
QED
==========================================================
Exercise: rev involutive
Claim: forall lst, rev (rev lst) = lst
Proof: by induction on lst
P(lst) = rev (rev lst) = lst
Base case: lst = []
Show: rev (rev []) = []
rev (rev [])
= { eval rev, twice }
[]
Inductive case: lst = h :: t
Show: rev (rev (h :: t)) = h :: t
IH: rev (rev t) = t
rev (rev (h :: t))
= { eval rev }
rev (rev t @ [h])
= { exercise 3 }
rev [h] @ rev (rev t)
= { IH }
rev [h] @ t
= { eval rev }
[h] @ t
= { eval @ }
h :: t
QED
==========================================================
Exercise: reflect size
Claim: forall t, size (reflect t) = size t
Proof: by induction on t
P(t) = size (reflect t) = size t
Base case: t = Leaf
Show: size (reflect Leaf) = size Leaf
size (reflect Leaf)
= { eval reflect }
size Leaf
Inductive case: t = Node (l, v, r)
Show: size (reflect (Node (l, v, r))) = size (Node (l, v, r))
IH1: size (reflect l) = size l
IH2: size (reflect r) = size r
size (reflect (Node (l, v, r)))
= { eval reflect }
size (Node (reflect r, v, reflect l))
= { eval size }
1 + size (reflect r) + size (reflect l)
= { IH1 and IH2 }
1 + size r + size l
size (Node (l, v, r))
= { eval size }
1 + size l + size r
= { algebra }
1 + size r + size l
QED
==========================================================
Exercise: propositions
type prop = (* propositions *)
| Atom of string
| Neg of prop
| Conj of prop * prop
| Disj of prop * prop
| Imp of prop * prop
Induction principle for prop:
forall properties P,
if forall x, P(Atom x)
and forall q, P(q) implies P(Neg q)
and forall q r, (P(q) and P(r)) implies P(Conj (q,r))
and forall q r, (P(q) and P(r)) implies P(Disj (q,r))
and forall q r, (P(q) and P(r)) implies P(Imp (q,r))
then forall q, P(q)
==========================================================
Exercise: list spec
Operations:
module type List = sig
type 'a t
val nil : 'a t
val cons : 'a -> 'a t -> 'a t
val append : 'a t -> 'a t -> 'a t
val length : 'a t -> int
end
Equations:
1. append nil lst = lst
2. append (cons h t) lst = cons h (append t lst)
3. length nil = 0
4. length (cons h t) = 1 + length t
==========================================================
Exercise: bag spec
Generators: `empty`, `insert`.
Manipulator: `remove`.
Queries: `is_empty`, `mult`.
Equations:
1. is_empty empty = true
2. is_empty (insert x b) = false
3. mult x empty = 0
4a. mult y (insert x b) = 1 + mult y b if x = y
4b. mult y (insert x b) = mult y b if x <> y
5. remove x empty = empty
6a. remove y (insert x b) = b if x = y
6b. remove y (insert x b) = insert x (remove y b) if x <> y
7. insert x (insert y b) = insert y (insert x b)